Pyrosequencing analysis of BRCA1 methylation level in breast cancer cells - Cai, Fengfeng; Ge, Isabell Xiang; Wang, Minghong; Biskup, Ewelina; Lin, Xiaoyan; Zhong, Xiaoyan (Tumor biology, 2014)
BRCA1 and BRCA2 genes are crucial for double-strand break repair by homologous recombination, and mutations in these genes are responsible for most familial breast carcinomas. Cells with inactivating mutations of the BRCA1 or BRCA2 tumor suppressor genes are sensitive to poly (ADP-ribose) polymerase-1 (PARP1) inhibitors. Already in 2010, it has been predicted, that BRCA1 hypermethylation might be sensitive to PARP1 inhibitor. However, till today, a statistically significant proof has been missing, and the effectiveness of PARP1 inhibitors for breast cancer caused by BRCA1 promoter hypermethylation remained elusive. Pyrosequencing has been proposed as an optimal method to investigate the methylation status of the BRCA1 genes. Here, we show for the first time that BRCA1 CpG island hypermethylation is sensitive to PARP1 inhibitors. In clinical settings, this might improve treatment response and provide a more personalized therapy for breast cancer patients. Furthermore, the determination of methylation status of BRCA1 and other genes of the BRCA/homologous recombination (HR) pathway may be an important predictive classifier of response to PARP inhibitor therapy.
Published online: 15 December 2013
Gesehen am 25.08.2020